Horticultural therapy as a tool of healing persons with disability on an example of Support Centre in Kownaty - Suchocka, Marzena; Kosiacka-Beck, Ewa; Niewiarowska, Anna (Ecological Questions, 2019)
Nowadays, the interest in nature’s impact on our mental and physical health is getting more and more common worldwide. The nature is able to relax, gentles nerves, arouses positive emotions. Greenery is a basic and most valuable part of human lives, which accompanies people and also a priceless space both, near single-family houses and public spaces as well. Scientific studies shows, that a contact with nature may approve social function, has an influence on our mood, physical health, mental condition, reduces stress and pressure. It gives us many benefits on mental, physical and intellectual ground. Horticultural therapy is a supportive element and such an effective method in healing many afflicions and rehabilitation proces. In horticultural therapy it is possible to use tasteful values, which references to landscape’s charm, greenery composition and single plants, their flavor, colours and textures. Beneficent impact of plants is connected to incentives, which influence on people and to the large variety of activities related to the plants care. In this type of horticultural therapy, we must take into account all aspects connected to design – personalised by exact needs of user, adjusted to dysfunctions and possibilities of people, who takes a use of therapy in garden. The present studies shows that guidelines to therapeutic garden design must result from many spatial and greenery analysises, assessment of posssibilities and limits of the place, the way of its actual use and strict cooperation between the gardener and therapist. We assumed that designer should participate very actively in the therapy of potential users in order to know the specification of desease